SOLUBILITY AND TRANSPORT OF PLATINUM-GROUP ELEMENTS IN SUPERCRITICAL FLUIDS: SUMMARY AND ESTIMATES OF THERMODYNAMIC PROPERTIES FOR RUTHENIUM, RHODIUM, PALLADIUM, AND PLATINUM SOLIDS, AQUEOUS IONS, AND COMPLEXES TO 1000OC AND 5 KBAR - RECENT EXPERIMENTAL CONSTRAINTS AND A RE-EVALUATION OF THEORETICAL PREDICTIONS - Sassani D.C.; Shock E.L. (My University, 1998)
Several correlation methods are used to estimate data and equation-of-state parameters that permit calculation of standard state thermodynamic properties at high pressures and temperatures for metals, oxides, and sulfides, as well as ions, and aqueous chloride, hydroxide, and sulfate complexes of Ru+2, Ru+3, Rh+2, Rh+3, Pd+2, and Pt+2. Estimates are based on a critical review of data from the literature at 25°C and 1 bar. The combined data for 14 minerals, 6 cations, and 56 aqueous complexes provide a foundation for quantitative predictions of aqueous speciation of these platinum group elements (PGE), as well as platinum group mineral (PGM) solubilities as functions of pH, oxidation state, and chloride and sulfate content of geologic fluids at temperatures to 1000°C and pressures to 5 kbar. Therefore, these estimates are the first to address PGE speciation at the pressure and temperatures of most PGM deposits. Comparisons are made to other theoretical predictions of platinum-group element (PGE) complex formation in aqueous solutions and to pertinent experimental data. We conclude that Pd-chloride complexes may be less stable at lower temperatures than previously predicted by other investigators, but that Pt-chloride complexes may be considerably more stable.